2015
DOI: 10.1021/jacs.5b07498
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Adjacent Quaternary Stereocenters by Catalytic Asymmetric Allylboration

Abstract: Allylboration of ketones with γ-disubstituted allylboronic acids is performed in the presence of chiral BINOL derivatives. The reaction is suitable for single-step creation of adjacent quaternary stereocenters with high selectivity. We show that, with an appropriate choice of the chiral catalyst and the stereoisomeric prenyl substrate, full control of the stereo- and enantioselectivity is possible in the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 51 publications
1
65
0
Order By: Relevance
“…Chong5b and Wu have reported on the asymmetric allylboration of cyclic imines using BINOL modified allylboronates whereas the Schaus group8 described the BINOL‐catalyzed asymmetric crotylboration of highly reactive acyl imines. These studies, together with our previous experience,2 suggested that BINOL‐catalyzed allylborations are a promising synthetic method for the catalytic asymmetric allylation of indoles with allylboronic acids.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Chong5b and Wu have reported on the asymmetric allylboration of cyclic imines using BINOL modified allylboronates whereas the Schaus group8 described the BINOL‐catalyzed asymmetric crotylboration of highly reactive acyl imines. These studies, together with our previous experience,2 suggested that BINOL‐catalyzed allylborations are a promising synthetic method for the catalytic asymmetric allylation of indoles with allylboronic acids.…”
mentioning
confidence: 79%
“…Interestingly, commercially available 3 a has been shown to be one of the best catalysts for the asymmetric allylboration of ketones as well 2. Performing the reaction in the absence of methanol substantially decreased the selectivity from 99 % ee to 56 % ee (compare entries 1 and 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Szabó et al . reported the synthesis of adjacent quaternary stereocenters in 125 by asymmetric organocatalyzed allylboration of ketones 123 with γ,γ‐disubstituted allylboronic acids 124 (Scheme ) . Full control of the diastereo‐ and enantioselectivity was achieved in a stereodivergent approach by the choice of the BINOL catalyst and the diastereoisomeric prenylboronic acid.…”
Section: Asymmetric Organocatalytic 12‐additionsmentioning
confidence: 99%